2011
DOI: 10.1128/jvi.05040-11
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Swine Major Histocompatibility Complex Class I SLA-1*0401 and Identification of 2009 Pandemic Swine-Origin Influenza A H1N1 Virus Cytotoxic T Lymphocyte Epitope Peptides

Abstract: The presentation of viral epitopes to cytotoxic T lymphocytes (CTLs) by swine leukocyte antigen class I (SLA I) is crucial for swine immunity. To illustrate the structural basis of swine CTL epitope presentation, the first SLA crystal structures, SLA-1*0401, complexed with peptides derived from either 2009 pandemic H1N1 (pH1N1) swine-origin influenza A virus (S-OIV NW9 ; NSDTVGWSW) or Ebola virus (Ebola AY9 ; ATAAATEAY) were determined in this study. The overall peptide-SLA-1*0401 structures resemble, as expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(96 citation statements)
references
References 72 publications
5
89
1
1
Order By: Relevance
“…The gel filtration and SDS-PAGE results showed that the peak represented the complex of Anpl -UAA*01 and Anpl -β2m (Fig. 3), which is different from results of studies on cattle, pig, chicken, and horse pMHC I refolding (33, 3941). This result could be due to the Cys 95 -Cys 112 disulfide bond of p Anpl -UAA*01.…”
Section: Resultscontrasting
confidence: 74%
“…The gel filtration and SDS-PAGE results showed that the peak represented the complex of Anpl -UAA*01 and Anpl -β2m (Fig. 3), which is different from results of studies on cattle, pig, chicken, and horse pMHC I refolding (33, 3941). This result could be due to the Cys 95 -Cys 112 disulfide bond of p Anpl -UAA*01.…”
Section: Resultscontrasting
confidence: 74%
“…Previously, we also found a peptide-selecting role for the D pocket of the swine MHC class I molecule p/SLA-1*0401 (Fig. 8C), although, like in some other p/MHC I with established roles of pocket D in peptide selection, in p/SLA-1*0401 other pockets also have an important anchor position role (10). In contrast, our current set of data indicate that in p/UAA-b2m the only dominant anchor position may be pocket D, which together with the hydrogen bond between pocket D Y99 and P3N (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The p/UAA-b2m crystal structure was solved by molecular replacement via the MOLREP program using SLA-1*0401 (Protein Data Bank [PDB] code: 3QQ3) as the search model (10). Extensive model building was manually performed with COOT (25), and restrained refinement was performed with REFMAC5.…”
Section: Structure Determination and Refinementmentioning
confidence: 99%
See 2 more Smart Citations